2022
DOI: 10.1039/d2ta05180j
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic selectivity for nitrogen reduction vs. hydrogen evolution: a comparison of vanadium and cobalt oxynitrides at different pH values

Abstract: The electrocatalytic nitrogen reduction reaction (NRR) is of significant interest as an environmentally friendly method for NH3 production for agricultural and clean energy applications. Selectivity of NRR vis-à-vis the hydrogen...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…Using analogous plane-wave DFT results, the stability of the critical diazenide *NNH surface configuration (computations assume zero applied potential pH = 0 to facilitate comparison) was compared for the various 3d metal oxynitrides our group has studied: 17 rs-TiO x N y (001), rs-VO x N y (001), zb-CoO x N y (110), and zb-CoN(110), zb = zinc blende.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using analogous plane-wave DFT results, the stability of the critical diazenide *NNH surface configuration (computations assume zero applied potential pH = 0 to facilitate comparison) was compared for the various 3d metal oxynitrides our group has studied: 17 rs-TiO x N y (001), rs-VO x N y (001), zb-CoO x N y (110), and zb-CoN(110), zb = zinc blende.…”
Section: Resultsmentioning
confidence: 99%
“…In previous experimental/computational studies of V-oxides and -oxynitrides it was concluded that N 2 /water binding was competitive under catalytic conditions. 17–19 In support of this hypothesis, N 2 and water binding energies for model surfaces of varying coordination number and formal oxidation state were evaluated. 17–19 N 2 binding was found to be favored for lower coordination numbers and less positive metal formal oxidation states, bonding characteristics that enhance π-backbonding from the metal to the N 2 π* orbitals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prospective candidates are ZrN, NbN, CrN, and VN enclosed with the RS(100) facets, which are calculated to be able to produce ammonia at −0.76 V, −0.65 V, −0.76 V, and −0.51 V, respectively (Figure 3A). [46] Most importantly, hydrogen evolution reaction (HER) is no longer the competing reaction on these TMN catalysts [80] . On the contrary, other TMNs, as well as the above‐mentioned ones in the ZB crystal structure or facets show poor or no catalytic activity, and/or catalyst decomposition occurs [44–46] .…”
Section: Theoretical Calculations Of Tmn Catalysts For Enrrmentioning
confidence: 99%
“…[46] Most importantly, hydrogen evolution reaction (HER) is no longer the competing reaction on these TMN catalysts. [80] On the contrary, other TMNs, as well as the above-mentioned ones in the ZB crystal structure or facets show poor or no catalytic activity, and/or catalyst decomposition occurs. [44][45][46] To further explore new candidates for ENRR at ambient conditions via the MvK mechanism, the catalytic performance of 23 TMNs with the ZB(110) facets are investigated.…”
Section: Catalytic Activitymentioning
confidence: 99%